Respuesta :
The first step you would take is to combine all like terms in the parentheses.
5a - 4a = a
Then you would multiply 2 by a, which would equal 2a.
Finally, combine all like terms (all terms with a), to get 8a. (2a + 6a = 8a)
Hope this helps!
5a - 4a = a
Then you would multiply 2 by a, which would equal 2a.
Finally, combine all like terms (all terms with a), to get 8a. (2a + 6a = 8a)
Hope this helps!
Hey there :)
We need to open the brackets and distribute the 2
However, we can see that both the terms within the parenthesis are like terms
5a - 4a = 1a or a
2(1a) + 6a
2a + 6a We can combine the like terms
= 8a
We need to open the brackets and distribute the 2
However, we can see that both the terms within the parenthesis are like terms
5a - 4a = 1a or a
2(1a) + 6a
2a + 6a We can combine the like terms
= 8a